INOVASI MESIN PENCACAH PAKAN TERNAK UNTUK MENINGKATKAN PRODUKTIVITAS PETERNAK KAMBING ETAWA DI DESA BANGUN SARI BARU KECAMATAN TANJUNG MORAWA, KABUPATEN DELI SERDANG, SUMATERA UTARA - dharma, surya; Razak, Abd.; Dithisari, Indri; Hartika, Lia; Rahmawaty, Rahmawaty; Hasibuan, Yetti Meuthia; Lubis, Riadini Wanty (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Sheep farming is a business that can provide economic improvement and welfare for the community in Deli serdang district in general and Bangun Sari Baru Village in particular. Raising sheep has advantages over other types of livestock, because sheep are easy to raise, breed quickly, have a market that is always available at any time and require relatively little capital when compared to larger ruminant livestock such as cattle. Sheep farming that has been carried out is greatly influenced by the existence of feed that is usually obtained from plantations in the surrounding environment which is decreasing in capacity due to land conversion. So far, sheep have been given feed in the form of green grasses, cassava leaves and elephant grass. However, a lot of leftover food is wasted because it cannot be consumed optimally by livestock such as cassava stalks at the ends and elephant grass stalks. Therefore, feed enumeration is very necessary to minimize wasted feed. In addition to obstacles in the provision of feed, another obstacle faced by partners is the need for hygienic milk packaging. Thus, the milk chopper and packaging machine is a solution that is considered to be able to solve the problems faced by goat farming partners, namely Mr. Abu Daud in Bangun Sari Baru Village, Tanjung Morawa District, Deli Serdang Regency.